Analisis Dampak Penambangan Pasir Ilegal Sungai Brantas terhadap Lingkungan Hidup di Desa Brumbung Kabupaten Kediri - Agus Abdul Halim; Nugroho Tri Waskitho; Galit Gatut Prakosa (Journal of Forest Science Avicennia, 2019)
Indonesia is a country with abundant natural resources, including those with enough potential, namely the mining sand industry. Mining on a large scale is good for economic growth, but vice versa on the environmental impacts caused. Environmental damage due to exploitation also occurred in Brumbung village, Kediri district. Environmental damage caused by existing sand mining creates problems that must be claimed by all parties. This paper examines how the impact caused by sand mining activities on the surrounding environment. This type of research is descriptive-qualitative, where the research process and understanding are based on the methodology that investigates a phenomenon. To study this problem, observations and questions and answers were made to the miners, the surrounding community and also the relevant offices. The observed location is around the Brantas River where there are sand mining activities in Brumbung Village, Kepung Subdistrict, Kediri District. research in the area is motivated by the phenomenon of the large number of illegal sand mining in the Brantas river, especially in the self-inflated village, which has many pros and cons in the surrounding community. The environment itself is all things, conditions, conditions and influences that are in the space we occupy and affect the things that live, including human life. Population growth has increased the need for clothing, food, shelter, clean water and energy. This results in higher exploitation of natural resources and tends to neglect environmental aspects. Therefore there is a need for research on the study of environmental impacts, both physical and socio-economic activities of sand mining in the berumbung village, in order to obtain an overview of the environmental impacts that occur or will occur. Later this research is to be taken into consideration in making policies related to the problem of sand mining.